Processo erosivo: estudo de caso da estrada de acesso a cascata do salso – Caçapava do Sul, RS - (:unkn) unknown (Universidade Federal do Pampa, 2018)
Brazil has great potential for the development of different types of tourism. The municipality of Caçapava do Sul, located in the central-southern region of the State of Rio Grande do Sul, stands out for its geodiversity, which presents approximately 46 geosites. The Cascata do Salso was characterized as one of these geosites, with a beautiful waterfall of more than 20 meters. Its access is through a dirt road that is in a precarious situation, and has undergone an intense erosive process. The first five kilometers of the route are in good condition. It is in the final stretches, approximately in the last 800 meters, that the conditions are impassable. The objective of this work was to perform a geological-geotechnical diagnosis of the present situation of the road in order to propose measures to reduce erosion and to provide subsidies for the use of more appropriate techniques that could reduce its fragile conditions, as well as to minimize the environmental impacts. The methodology applied in this work consisted of the physical characterization for the three horizons of the samples collected in the field, and for the other tests: disintegration, MCT erodibility criterion (infiltrability and immersion), laboratory cone and inderbitzen, C, because the road is situated on the same, in addition, the geophysics was made through the electric path - CE. From the results obtained in the tests and also in the field analysis, it can be concluded that the road has undergone a highly intensified erosive process, as can be observed by the MCT criterion, a pi / s ratio between 191.1 g / cm² / min / Pa and 371,17 g / cm² / min / Pa, being considered as erodible soil when it has a value higher than 52. In addition, the road has been supported by pegmatite veins, but with signs of weathering, not presenting great stability. Therefore, it can be concluded that the erosion process on the road of the Cascata do Salso was intensified due to the anthropic intervention that altered the original profile of this access; in addition, the lack of drainage channel speeds up this process. Finally, it is suggested as a measure to mitigate this intense erosive process, a work of shifting, to help stabilize the slope and, later, the implementation of a structure of Paliçada with geotextile, which helps to slow the flow of water and retain part of the sediments carried by it, allowing the stabilization of the local soil.
Keywords: Erosão; Estrada; Geológico-geotécnico; Erosion; Road; Geological-geotechnical; CNPQ::CIENCIAS EXATAS E DA TERRA